2019
DOI: 10.1007/s12020-019-01880-6
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the JAK2/STAT3-CAV-1-NR2B signaling pathway in painful diabetic neuropathy

Abstract: Purpose The aim of the present study was to further elucidate the role of JAK2/STAT3-CAV-1-NR2B on painful diabetic neuropathy. Methods In vivo, the mechanical withdrawal threshold and thermal withdrawal latency were measured to evaluate neuropathic pain behaviors ( n = 8), while western blot ( n = 5) and an immunofluorescence double staining experiment ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…44,52 A rapidly growing body of evidence showed that microglial cells are critical components for hyperpathia and coexistence of STAT3 with microglia. 53,54 Our current immunofluorescence results showed that p-JAK2 and p-STAT3 were activated by BCP colocalized with astrocytes, microglial cells, and neurons in spinal dorsal horn. Vast majority of these proteins were located on the neurons, which may in turn cause hyperexcitability of neurons.…”
Section: Discussionmentioning
confidence: 70%
“…44,52 A rapidly growing body of evidence showed that microglial cells are critical components for hyperpathia and coexistence of STAT3 with microglia. 53,54 Our current immunofluorescence results showed that p-JAK2 and p-STAT3 were activated by BCP colocalized with astrocytes, microglial cells, and neurons in spinal dorsal horn. Vast majority of these proteins were located on the neurons, which may in turn cause hyperexcitability of neurons.…”
Section: Discussionmentioning
confidence: 70%
“…It was further demonstrated that the CAV1-NR2B pathway is activated by microglial JAK2-STAT3 signaling (Janus kinase 2-signal transducer and activator of transcription 3), which contributes to diabetic neuropathic pain. Pain was also relieved by administering AG490 (JAK2 inhibitor) to the rats [193]. Collectively these data render promising DPN therapies based on the JAK2-STAT3-CAV1-NR2B signaling pathway.…”
Section: Role Of Caveolin-1 In Oxidative Stressmentioning
confidence: 85%
“…Furthermore, the cytokines further activate glial cells and neurons to release more activating substances, such as ATP, pro-inflammatory factors and reactive oxygen species ( 42 ). These activating substances further enhance pain and may transform acute pain into chronic pain ( 43 ). In the present study, the expression levels of the inflammatory factors IL-6 and TNF-α not only increased in the DRG, but also in the tissues surrounding incision after noxious injury, which provided evidence towards the aforementioned hypothesis.…”
Section: Discussionmentioning
confidence: 99%